Using Agent-Based Models to Design Social Marketing Campaign. Issue 1 (February 2014) - Perez-Mujica, Luisa; Duncan, Roderick; Bossomaier, Terry
Community-based social marketing (CBSM) involves members of the community as active participants in the marketing campaign for a social good. However behaviour of community members in CBSM is not well simulated using the standard tools available to marketers. We show how agent-based models (ABMs) can be used to simulate the behaviour of community members at the individual level to determine how sensitive the outcome of a CBSM campaign is to assumptions around the effectiveness of marketing within the community. We develop an ABM for wetlands managers to use to simulate the outcome of a marketing plan for promotion of environmental tourism in a wetlands area. The wetlands managers must trade off the costs of marketing and the damage done by the tourism activities with the value of ecotourism for the wetland. We find evidence from the simulations that wetlands' ecological health is sensitive to the design of the social marketing campaign.